Clinical applications for magnetic resonance guided high intensity focused ultrasound (MRgHIFU): Present and future. Issue 4 (22nd July 2013) - Ellis, Samantha; Rieke, Viola; Kohi, Maureen; Westphalen, Antonio C
Summary It has been well known for decades that high intensity focused ultrasound (HIFU) generates heat in tissues resulting in coagulative necrosis. Implementation, however, has been slow, due to difficulties with finding an appropriate imaging modality that could not only guide treatment, but also provide real‐time thermal feedback. These problems have been overcome with the newest magnetic resonance‐guided high intensity focused ultrasound systems (MRgHIFU). With its superior spatial resolution enabling accurate image guidance coupled with its ability to provide real‐time thermography during treatments, MRI is moving further into the realm of therapeutics for oncologic patient care. This article will discuss the implementation of an MR‐guided HIFU system, current clinical indications and touch on future directions.